1993
DOI: 10.1109/10.245636
|View full text |Cite
|
Sign up to set email alerts
|

Effects of induced electric fields on finite neuronal structures: a simulation study

Abstract: In this paper we present an analysis of magnetic stimulation of finite length neuronal structures using computer simulations. Models of finite neuronal structures in the presence of extrinsically applied electric fields indicate that excitation can be characterized by two driving functions: one due to field gradients and the other due to fields at the boundaries of neuronal structures. It is found that boundary field driving functions play an important role in governing excitation characteristics during magnet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
118
0
2

Year Published

1999
1999
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 179 publications
(134 citation statements)
references
References 37 publications
14
118
0
2
Order By: Relevance
“…In particular, one should not make use of varied scalp to cortex distance to infer a single, general stimulus intensity versus depth relationship. In vitro experimental and modeling data suggests that the site of activation is predicted by the peak electric field magnitude (Amassian et al 1992;Maccabee et al 1993;Nagarajan et al 1993;Nagarajan and Durand 1995). Moreover, in vivo TMS experiments in both the motor and visual cortex have provided evidence that stimulation occurs at the location of the peak electric field (Wassermann et al 1996;Krings et al 1997;Boroojerdi et al 1999).…”
Section: Discussionmentioning
confidence: 99%
“…In particular, one should not make use of varied scalp to cortex distance to infer a single, general stimulus intensity versus depth relationship. In vitro experimental and modeling data suggests that the site of activation is predicted by the peak electric field magnitude (Amassian et al 1992;Maccabee et al 1993;Nagarajan et al 1993;Nagarajan and Durand 1995). Moreover, in vivo TMS experiments in both the motor and visual cortex have provided evidence that stimulation occurs at the location of the peak electric field (Wassermann et al 1996;Krings et al 1997;Boroojerdi et al 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Several articles are available that address boundary condition modeling [51][52][53][54][55][56]. The interested reader is referred to them for more information.…”
Section: Magnetic Modelingmentioning
confidence: 99%
“…1a). Furthermore, as pointed out by Nagarajan et al [8], at the neuronal terminals where the induced current #ows toward (away from) them, magnetic stimulation results in the equivalent amount of current injection (subtraction) (Fig. 1b).…”
Section: Simulation Of Magnetic Stimulationmentioning
confidence: 99%
“…Biophysical mechanism underlying its e!ect is, however, largely unknown. Previous theoretical studies [10,8] have demonstrated that a brief magnetic pulse (less than 1 ms duration), commonly used in TMS, can generate an action potential in a straight axonal "ber. Nevertheless, TMS typically demonstrates e!ects including a long inhibitory period (a few hundred ms) as observed in EMG [3] and visual perception [1,5].…”
Section: Introductionmentioning
confidence: 99%